Interview with Dr. Magdolna Csath, Professor - Trautmann, László; Csath, Magdolna (Public Finance Quarterly, 2025)
Magdolna Csath graduated from the Marx Károly University of Economics in 1966 and studied applied mathematics at the Eötvös Loránd University in 1967-68. In 1969, she won the national competition „Young People’s Competition in Economics” organised by Hungarian television. In 1972-73, she completed the MBA programme at the London Business School (England). In 1996, she was awarded a Habilitation in Economics at the Budapest University of Economics and Business Administration. She received her doctorate in economics from the Hungarian Academy of Sciences in 1991. Between 1999 and 2002, she was awarded a Széchenyi Professorship Fellowship to support her teaching and research work. She taught for five years in the USA and one year in Great Britain. In the USA she was awarded the „L. J. Buchan Distinguished Professorship Award”. She received the Albert Szent-Györgyi Award in 2008 and the „For the Hungarian Economy” Award in 2015. She is an advocate of development as opposed to growth at any price. She believes that the economy exists to serve the people, rather than the people exist to serve the economy. She is particularly interested in the possibility of developing the Hungarian economy based on knowledge, innovation and people. She has published more than 100 papers in Hungary and abroad. She is the author and editor of the book „Regime change in the economy, or how Hungarian industry disappeared”, published by Kairosz Publishing House in 2015, and „Economics: social economics, macroeconomic foundations”, published by the National University of Public Service in 2014. Her most cited books are „Strategic Planning in the 21st Century”, „Competitiveness Management” (National Textbook Publisher 2010) and „Competitiveness Mosaic” (Academic Publishers 2023). Important recent papers include „Growth or Development Trap” (Financial and Economic Review 2022) and „The role of Intangible Capital Investment and Intangible Assets in Improving Competitiveness” (Financial and Economic Review 2023). She is a Private Professor at the National University of Public Service and a lecturer at the Pázmány Péter Catholic University. Member of the National Competitiveness Council from 2017 to 2022.